2009
DOI: 10.1002/jso.21239
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic colorectal carcinomas with low‐level microsatellite instability in Korea: Do they form a distinct subgroup with distinguished clinicopathological features?

Abstract: These results indicated that sporadic MSI-low CRCs in Korea displayed distinguished clinicopathological features and might form a distinct subgroup especially from MSS CRCs. Further large studies are required to evaluate the impact of MSI-low status on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
4
9
1
Order By: Relevance
“…MSI assay is used as a prognostic marker for CRC. In contrast to MSI‐H CRCs with favorable prognosis (Boland et al, ), along with our results, some studies stated MSI‐L CRCs are associated with poorer OS (Garcia et al, ; Kohonen‐Corish et al, ; S. Y. Lee et al, ; Mojarad et al, ; Ok et al, ; Wright et al, ), whereas Y. H. Kim et al () did not find any significant differences and Azzoni et al () justified MSI‐L CRCs are associated with favorable oncologic outcomes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…MSI assay is used as a prognostic marker for CRC. In contrast to MSI‐H CRCs with favorable prognosis (Boland et al, ), along with our results, some studies stated MSI‐L CRCs are associated with poorer OS (Garcia et al, ; Kohonen‐Corish et al, ; S. Y. Lee et al, ; Mojarad et al, ; Ok et al, ; Wright et al, ), whereas Y. H. Kim et al () did not find any significant differences and Azzoni et al () justified MSI‐L CRCs are associated with favorable oncologic outcomes.…”
Section: Discussionsupporting
confidence: 75%
“…However, the reported prevalence varies according to ethnicity, number of markers, and the panels that were used for the MSI (Azzoni et al, 2011;Kets et al, 2006;Y. H. Kim et al, 2009;Mojarad et al, 2016;Rudzki et al, 2003), our results confirmed that tumors classified as MSI-L are a distinct molecular group with different clinicopathological features, however, other studies did not support the discrimination of MSI-L from MSS tumors in clinicopathological features (Kambara et al, 2001;S.…”
Section: Discussionsupporting
confidence: 70%
“…Several criteria are used to define MSI. In the report by Gafa et al it is mentioned as an independent prognostic factor,60 while Kim et al could not demonstrate an effect on survival in CRC 61. Four studies on the relation between MSI and survival in MAC were included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous differentiation results in a 2–8% increased hazard of death, which persists after correction for stage. Although the relation between MAC and MSI was clearly demonstrated,10 61 65 the combined effect of MAC and MSI on survival is less studied. Our systematic search identified only four publications addressing this subject.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MSI in endometrial polyps was 6.4% (6/109), and all polyps were MSI-low. The biological significance of MSI-low in colorectal carcinoma has been conflicting because although MSI-low seemed to be located in the “gray zone” between MSS and MSI-high, the sporadic MSI-low displayed clinicopathological features and might form a distinct subgroup [17]. The prevalence of MSI-low in sporadic endometrial carcinoma varies between 10 and 30%, but its clinical and histopathological significance are not clear [5,15].…”
Section: Commentsmentioning
confidence: 99%